Food recipe mobile application for the senstives using Application Programming Interface (API) / Muhamad Harith Noor Affandee - Noor Affandee, Muhamad Harith (2022)
Geographical background and religions make us human different from one another. This diversity plays many roles in affecting our diet and disease. Health issues are often related to a person of dietary pattern. Some growth to be stronger but some become sensitives to these changes. People that develop allergy reaction often have limited access to certain type of food. This group of people is minority compared to others. Due to limited access of food this people choose to have certain diet adjusting with their body. This project presents an application that can assist people with strict dietary and allergies problem to find suitable recipes for them. Reliable and accurate food data source is gathered and used in this mobile application. Android environment will be the main focus for this project and application programming interface serve as medium to interact with the application developed. Proper planning, design, implementation, and testing steps are taken to ensure the reliability of the application. Charts and results are presented to show the functionality and acceptance of the works done. The application proof to be a reliable source and assist those affected by strict and sensitives food dietary. Despite the great outcome, there is still some limitation and updates that can further increase the value of this project.